PWE-104 Prevalance and significance of sessile serrated lesions from a large prospective UK series in the setting of bowel cancer screening programme. (28th May 2012) - Tholoor, S; Basford, P; Bhandari, P
Abstract : Introduction: Screening colonoscopy has not had a big impact in reducing right sided cancer mortality and it is believed that this could partly be due to sessile serrated lesions (SSLs) which are thought to be the precursors of microsatellite adenocarcinomas. In the UK, people from the age of 60 to 75 with positive faecal occult blood undergo screening colonoscopy. We aim to evaluate the prevalence and significance of SSLs in our screening population. Methods: All colonoscopies performed between 2007 and 2011 were prospectively recorded on a screening database along with the histology. Pathology was reported as per standards laid out by the National screening programme by accredited Pathologists. Results: We analysed 1948 polyps from a total of 1576 patients. 28/1948 polyps in 25/1576 patients were found to have sessile serrated lesions. This amounted to 1.4% of the total polyps found. Out of 25 patients, 13 patients were men. The prevalence of sessile serrated lesions in all patients with polyps was 1.7% 17/28 lesions. (60%) of the lesions were smaller than 10 mm. 17/28 (60%) were in the right colon. 14/28 (50%) had no dysplasia. 14/28 (50%) had low grade dysplasia. None had high grade dysplasia or cancer. No interval cancer was found in a mean follow-up of 12 months. All 25 patients with sessile serrated lesions were also found to have conventional adenomas. 1–2 adenomas were found in 6/25 patients, 3–4 adenomas in 6/25 patients and 13/25 patients had at least 5 adenomas. Prevalance of dysplasia: SSLs with dysplasia: 14/28 (50%) –Low grade dysplasia: 14/14, High grade dysplasia/cancer: 0/14 SSLs with NO dysplasia: 14/28 (50%). Conclusion: (1) Our study shows a low prevalence of 1.7% of sessile serrated lesions accounting to <1.5% of the total number of polyps found in the setting of bowel cancer screening programme. (2) We did not find any high grade dysplasia or cancer in these patients. No interval cancer or synchronous cancers were found. (3) All patients with SSLs had conventional adenomas and the presence of SSLs had no effect on their surveillance plans. (4) Our study does not show any clinical impact of the sessile serrated lesions on patient outcomes. This questions the clinical relevance of SSLs. Competing interests: None declared. References: 1. Lash RH, Genta RM, Schuler CM. Sessile serrated adenomas: prevalence of dysplasia and carcinoma in 2139 patients. J Clin Pathol 2010;63 :681–6. 2. Freeman HJ . Heterogeneity of colorectal adenomas, the serrated adenoma, and implications for screening and surveillance. World J Gastroenterol 2008;14 :3461–3.